(untitled) (International Journal of Built Environment and Sustainability, 2022)
Trace the timeline of a pandemic such as Ebola, SARS, and SARS-CoV-2. All these extremely infectious viruses led to a worldwide pandemic starting in 2002. All these three viruses are transmitted to humans by animals from the jungle. The novel human coronavirus COVID-19 is now the fifth documented pandemic since the 1918 influenza pandemic. Questions about pandemics are on the rise these days, and it is widely discussed in the media. Recently, awareness about urban green spaces is rising in this era, and numerous researchers claim that appropriate landscape planning and design with the conception of sustainability able to produce a beneficial and responsive environment for healthy urban improvement in relation to pandemic crises. Therefore, this paper aims to investigate the effectiveness of urban green spaces for sustainable environmental health. The result shows that the role of urban green spaces improves immune system function, increases social capital and cohesion, reduces mortality, and increases life expectancy, reduces potential negative health impacts, and makes urban beautification healthier. In addition, the finding shows the benefits of urban green spaces in pandemics, for example improving mental health and stress reduction, improving physical health, decreasing the risk of disease transmission, and improving social cohesion.